Morphological and distributional patterns of native and invasive Trifolium (Papilionoideae, Leguminosae) species in southern South America. Issue 1 (31st December 2022) - De Diego, Fernando Carlos; Robbiati, Federico Omar; Gaitán, Juan José; Fortunato, Renée Hersilia
Abstract : The ability of a species to colonize new geographical areas is closely related to its morphological response to environmental gradients. Previous studies compared native and alien invasive species in their ability to modify their morphology in reaction to climatic and edaphic factors; however, taxonomically close species have been scarcely analyzed. In this study, morphological variability patterns associated with abiotic factors were evaluated in Trifolium polymorphum, a native species distributed from southern Brazil to northern Patagonia, and Trifolium repens, a species introduced as an important forage crop and naturalized in diverse environments of southern South America. A morphometric study was carried out using herbarium specimens that were then georeferenced to obtain environmental and distributional data. Morphological traits along abiotic and geographical gradients were analyzed, predictive distribution and current and future niches were modelled. Our results showed that leaf morphology of T. repens responds to precipitation and temperature factors, which could explain its invasive behavior in a wide range of environments. Morphological variability of the native T. polymorphum presented a low association with abiotic factors, suggesting possible difficulties in adapting to future environmental changes. Ecological niche modelling analysis showed several overlap areas between species in the current model and a greater expansion of the distribution range of the invasive species in future climate change scenarios.